Characteristics of Analog Jerky from Moringa Leaves (Moringa Oleifera L.) with the Addition of White Oyster Mushroom (Pleurotus Ostreatus) Powder - Rici Elvinas; Kesuma Sayuti; Fauzan Azima (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2022)
This study aims to determine the effect of differences of white oyster mushroom powder addition to the characteristic of beef jerky analog from Moringa leaves and to determine the best beef jerky analogs of moringa leaves with white oyster mushroom powder addition based on chemical, physical, and organoleptic analysis. This research used a Completely Randomized Design (CRD) with 4 treatments (the addition of white oyster mushroom 0%, 40%, 50%, and 60%) with 5 replications. The research data were analyzed using ANOVA and if it had significantly different, continued with Duncan's New Multiple Range Test (DNMRT) at a 5% significance level. The observation showed that the addition of white oyster mushroom powder had a significant effect on water content, ash content, fat content, protein content, crude fiber content, yield, and organoleptic on color, aroma, and taste, but it has no significant effect on the hardness and organoleptic texture. The best beef jerky analogs of moringa leave with white oyster mushroom powders based on chemical, physical, and organoleptic was beef jerky of D treatment (addition white oyster mushroom powder 60%) with characteristics of average yield 68.87%, hardness 39.01 %, water content 3.63%, ash content 6.38%, fat content 14.25%, protein content 15.01%, crude fiber content 8.14%, organoleptic of color 4.05 (like), aroma 3,90 (like), taste 3,35 (neutral), and texture 3,85 (like). Keywords: White oyster mushroom, Characteristic, Moringa leaves, Jerky analog